An Overview of Analytical Determination of Diltiazem, Cimetidine, Ranitidine, and Famotidine by UV Spectrophotometry and HPLC Technique - Nighat Shafi; Farhan Ahmed Siddiqui; Huma Naseem; Nawab Sher; Arif Zubair; Azhar Hussain; Ali Akbar Sial; Mirza Tasawer Baig (Journal of Chemistry)
This review article recapitulates the analytical methods for the quantitative determinations of diltiazem and three H2 receptor antagonists (cimetidine, ranitidine, and famotidine) by one of the spectroscopic technique (UV spectrophotometery) and separation technique such as high-performance liquid chromatography (HPLC). The clinical and pharmaceutical analysis of these drugs requires effective analytical procedures for quality control, pharmaceutical dosage formulations, and biological fluids. An extensive survey of the literature published in various analytical and pharmaceutical chemistry-related journals has been compiled in its review. A synopsis of reported spectrophotometric and high-performance liquid chromatographic methods for individual drug is integrated. This appraisal illustrates that majority of the HPLC methods reviewed are based on the quantitative analysis of drugs in biological fluids, and they are appropriate for therapeutic drug monitoring purpose.